Human Resource Management Practices and Innovation: A Review of Literature - Arulrajah, A. (University of Sri Jayewardenepura, Nugegoda., 2014)
The objective of this review is to explore the theoretical and empirical findings of research work, which link human resource management (HRM) practices with organisational innovation. Innovation models demand innovation oriented and focused bundles of HRM practices to develop and sustain innovation potential and capacity of organisations. Findings of this review reveal that the theoretical and empirical status of HRM practices on development and retention of innovation potential and capacity of organizations, and further enhances the existing body of knowledge and the literature on the relationship between HRM practices and organisational innovation. In addition, this review demonstrates three key roles of HRM practices on organisational innovation.
Keywords: Innovation; Human Resource Management; Human Resource Management Practices; Organisation